Aeration and agitation in hydroponic culture have detrimental effects on iron uptake - Langenfeld, Noah James; Bugbee, Bruce (Frontiers in Plant Science, 2025)
Aeration in deep-flow liquid hydroponics provides oxygen for respiration, but even gentle movement from solution agitation can alter the beneficial rhizosphere. Here we report the detrimental effects of bubbling-induced agitation of the rhizosphere on iron uptake and chlorosis of tomato, sunflower, and corn. We grew each species in deep-flow liquid hydroponics with aeration rates from 0 to 2 liters per minute and in a peat-based soilless media, which allowed plants to develop an undisturbed rhizosphere. All three species had ample iron and chlorophyll in soilless media with the same nutrient solution and pH as in liquid hydroponics. Conversely, chlorophyll and iron uptake were dramatically reduced in hydroponic sunflower and corn by gentle agitation of the solution. Tomato, however, was minimally affected by solution agitation. These results indicate that minimizing solution agitation allows the formation of a beneficial rhizosphere. Collectively, these studies demonstrate that controlled agitation might be used to alter root boundary layer thickness and thus quantify rhizosphere effects on nutrient uptake and growth.